Integration of Mahalanobis-Taguchi System and Time-Driven Activity-Based Costing in a Production Environment - Sri Nur Areena, Mohd Zaini; Filzah Lina, Mohd Safeiee; Ahmad Shahrizan, Abdul Ghani; Nur Najmiyah, Jaafar; Mohd Yazid, Abu (MDPI, 2023)
System integration is the act of combining numerous distinct subsystems into one bigger system that allows the subsystems to work together. The integrated system removes necessity of repeating operations. The purpose of this work was to investigate the best system integration in the production environment. A few methods were tested such as conventional, Mahalanobis-Taguchi System (MTS), Activity-Based Costing (ABC) and Time-Driven Activity-Based Costing (TDABC). As a result, critical activities may now be completed more effectively while reducing expenses. The organization should define the relation between cost and quality through system integration. As a consequence of system integration, four forms of integration are described, namely, integration A (conventional-ABC), integration B (conventional-TDABC), integration C (MTS-ABC), and integration D (MTS-TDABC). Integration D is the best in the production environment when compared to others because MTS recognizes the degree of contribution for each parameter that impacts the increase or decline in the final cost. Moreover, TDABC determines capacity cost rate from the costs associated with capacity provided, and time equations with versatility to dissipate the product’s complex nature. As a result of the integration of MTS and TDABC, various degrees of parameter contributions impact the time equations and capacity cost rate to generate a lower cost of product in the production environment.